Impact of the introduction of decoupled payments on functioning of the German land market: Country report of the EU tender Study on the functioning of land markets in those EU member states influenced by measures applied under the Common Agricultura; Auswirkung der Entkopplung von Direktzahlungen auf den Bodenmarkt in Deutschland Länderbericht des EU Tenders: "Studie der Funktionsweise der Bodenmärkte in den von den Maßnahmen der gemeinsamen Agrarpolitik betroffenen EU-Mitgliedsstaaten" - Lioudmila Möller; Sibylle Henriette Henter; Konrad Kellermann; Norbert Röder; Christoph Sahrbacher; Martin Zirnbauer (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Against the background of the reform of the Common Agricultural Policy (CAP) in 2003 the following analysis, brings into focus the responses of the agricultural sector to decoupled subsidies. In particular it addresses the impact of the Single Payment Scheme (SPS) on land sales and rent prices and therefore on farm structure. It also aims to assess the extent to which the reform advances sound and sustainable agriculture and provides incentives for marketorientated farming practices. The study is based on the analysis of statistical data and expert surveys conducted in three selected regions. – – Die vorliegende Studie untersucht den Einfluss der 2003 im Zuge der Reform der Gemeinsamen Agrarpolitik (GAP) durchgeführten Entkopplung der Direktzahlungen auf den Agrarsektor in Deutschland. Besonderer Fokus der Analyse liegt auf der Auswirkung der einmaligen Zahlungen auf die Kauf- und Pachtpreise für das landwirtschaftlich genutzte Land. Des Weiteren wird die Förderung einer nachhaltigen und marktorientierten Landwirtschaft durch die GAP-Reform bewertet. Die Untersuchung basiert auf Auswertung statistischer Daten und auf Expertenbefragungen, welche in drei ausgewählten Bundesländern durchgeführt wurden.
urn:nbn:de:gbv:3:2-10639
Keywords: Q15; Q18; 330; Land markets; midterm review; CAP; structural change; Bodenmärkte; Halbzeitbewertung; GAP; Strukturwandel